PERSPEKTIF RAFIQ AL-MISHRI TENTANG INFLASI DAN DAMPAKNYA TERHADAP AKTIVITAS INVESTASI - Ismail, Azmi (Institut PTIQ Jakarta, 2023)
This article aims to explain Rafiq al-Mishri's perspective on inflation. Inflation, apart from having an impact on deactivating the function of money, weakening the spirit of saving, increasing consumerist tendencies, and directing investment (capital investment) towards unproductive (land, buildings, precious metals, foreign currency) at the expense of productive investment, in agriculture, industry, trade, etc. The article uses the library research method, by collecting material from various sources then analyzing it and presenting it using a qualitative approach method. The results of the discussion explain that Rafiq al-Mishri's ideas and thoughts are good for in-depth study and development, because the world of investment is an important sector in human life because wealth in the perspective of Islam/sharia economics is not only to be sought and owned, but more than that for every human being. given the task of developing and empowering wealth so that he can prosper himself and others. The impact of inflation on investment activity is that it directs investment (capital investment) in an unproductive direction, and this phenomenon, seen from a sharia economic perspective, is not good for the economy and social welfare